2015
DOI: 10.1155/2015/891410
|View full text |Cite
|
Sign up to set email alerts
|

Co-UWSN: Cooperative Energy-Efficient Protocol for Underwater WSNs

Abstract: Sensor networks feature low-cost sensor devices with wireless network capability, limited transmit power, resource constraints, and limited battery energy. Cooperative routing exploits the broadcast nature of wireless medium and transmits cooperatively using nearby sensor nodes as relays. It is a promising technique that utilizes cooperative communication to improve the communication quality of single-antenna sensor nodes. In this paper, we propose a cooperative transmission scheme for underwater sensor networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 31 publications
0
63
0
Order By: Relevance
“…With the help of these packets, each sensor finds its optimal forwarders within its range of transmission and manages a list of forwarders under some threshold to find the best forwarder for its information forwarding (IF). Every sensor computes its weight function using expression 37 as follows …”
Section: Initialization Phasementioning
confidence: 99%
“…With the help of these packets, each sensor finds its optimal forwarders within its range of transmission and manages a list of forwarders under some threshold to find the best forwarder for its information forwarding (IF). Every sensor computes its weight function using expression 37 as follows …”
Section: Initialization Phasementioning
confidence: 99%
“…Simulation results showed that RACE routing scheme achieves improved packet delivery ratio, high stability period, less consumption of energy and low end-to-end delay as compared to AMCTD and ACE. In [3] the authors proposed a reliable, energy-efficient, and high throughput routing protocol Cooperative UWSN (Co-UWSN) for UWSNs to improve the performance of network. Distance and signal-to-noise ratio computation of the channel conditions are utilized by destination and relays nodes as cost functions.…”
Section: Related Workmentioning
confidence: 99%
“…<100 kHz) so all the sensor nodes are equipped with a low bandwidth acoustic modem therefore its propagation latency is five times higher than the radio channel i.e. sensor nodes can propagate upto 1 to 3 m/sec and they are generally considered as static [3]. Underwater nodes utilize more power and replacement of nodes or batteries is very difficult [7].…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Here a cost function has mentioned to select the very best route to sink calculated on the basis of their residential energy and their distance from the sink. Co-UWSN reduces effects of path loss and enhanced stability of the network [19].…”
Section: A Co-uwsnmentioning
confidence: 99%